Microbial Aromatization of Androsta-1, 4, 7- Triene-3, 17-Dione - Kluepfel, Dieter (1970)
Several microorganisms transform androsta-1, 4, 7-triene-3, 17-dione into equilin and equilenin, presumably via a 19-hydroxylated intermediate.